Effects of an organic modifier on body weight gain in zebu cattle in the tropics of Peru - Delgado C., Alfredo (2012)
The aim of this study was to evaluate the effects of a commercial organic modifier (Modivitasan) on body weight gain in zebu cattle. Thirty six Nellore steers were used. Animals were 25 ± 7.7 months old and had an initial body weight of 208.9 ± 40.2 kg. They were distributed in a treated group (n=20) that received three I.M. injections (1 ml/50 kg b.w.) of the organic modifier at 30 day-interval, and in a control non-treated group (n=16). Both groups were kept under a rotational grazing scheme in three paddocks with a mixture of Brachiaria decumbens, B. brizantha, Pueraria phaseloides, Paspalum plicatulum and Desmodium ovalifolium for 90 days. Animals were dewormed with 3.15% Ivermectin 15 days before the trial. Body weight gain in the treated group was 43.4 ± 9.2 kg and in the control group was 30.1 ± 5.4 kg (p<0.01). The superior body weight gain of the treated group could be explained for the additional supply of minerals, energy, vitamins and proteins contained in the organic modifier in a herd that was under detrimental nutritional conditions before the study. The use of the organic modifier would constitute an alternative for improving the efficient use of low quality pastures in the tropical lowlands of Peru.